ESTETIKA SENI EROTIS (EROTICA) : REPOSISI OTONOMI DAN HETERONOMI SENI ( UNTUK PERMASALAHAN ESTETIKA SENI EROTIS YANG DIANGGAP PORNOGRAFI) - Embun Kenyowati (Universitas Trisakti, 2011)
AbstractThis article discusses and reflect philosophically the aesthetic of erotic art phenomenon with considered as pornography by part of the member of society , which also has caused horizontal real conflict, because it is considered as inferting ethical ( moral) and political domain.Starting from the distiction between the aestheticof art based on the maxim